Alveolar Bone Density after the Orthodontic Treatment in Patients of Rsgm Universitas Airlangga - Ernie Maduratna Setiawatie; Mohamad Rubianto; Muhammad Naufal Ilmi Roswand (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: There is a relation between the orthodontic therapy and the periodontal tissue. In the movingteeth and planning treatment, the periodontal tissue is very influential in an orthodontic therapy. During themovement of the teeth, all components of the periodontal tissue such as the bones, periodontal ligaments,and gingiva will change and move together. Some studies indicate a decrease in alveolar bone fraction andalveolar bone density. The changes in density are seen by comparing the new bone mineralization withthe old bones. Purpose: This research aims to analyze the differences in alveolar bone density after anorthodontic treatment in patients of RSGM Universitas Airlangga. Methods: This study used a patient’spanoramic radiograph at the time before the orthodontic treatment and the time after it. Photographs ofpanoramic radiographs were measured using a digital densitometer. Results: The results of the studyrevealed a decrease in alveolar bone density after orthodontic treatment, both anterior and posterior. Theaverage decrease in the anterior was 35.4%, while in the posterior was a decrease of 31.5%. Conclusion:There was a decrease in the alveolar bone density after orthodontic treatment in the anterior and posteriorsections.